A comparison of the nucleotide sequence homologies of three isolates of bean yellow mosaic virus and their relationship to other potyviruses - Abu Samah, Norani; Randles, J. W. (Elsevier, 1981)
3H-labelled complementary DNA (cDNA) was reverse transcribed from the RNA of three biologically distinct isolates of bean yellow mosaic virus (BYMV-G, Q, and S) by the random primer method of Taylor et al. [Biochim. Biophys. Acta 442, 324-330 (1976)]. Excess virus RNA was hybridized with each of the cDNAs and percentage hybrid formation was assayed using the single-strand-specific nuclease S1, The R0t (1/2) values obtained for the homologous hybridization reactions (1.2 x 10(-2) mol sec liter(-1)) showed that all three BYMV-RNAs were unique species, without detectable zones of reiteration. Reciprocal hybridizations between isolates G, Q, and S have shown that each was significantly different from the other. A comparison of these three isolates with a selection of other potyviruses showed that the relationship between them was closer than that observed between any of them and the other potyviruses tested.